REASONABLE DESIGN METHOD OF BOX CRANE GIRDER BY TAGUCHI METHOD - Giang, Dương Trường (Journal of Applied Engineering Science, 2024)
Overhead cranes are widely used in industrial systems. In this study, the research object is the main box girder of the overhead crane. The research objective is to find the parameters to obtain a lighter structure, which reduces the market price of the crane. The article studies the method of calculating crane girders and sets up the optimization algorithm. The study will use the Taguchi method, and ANOVA analysis to evaluate the influence of box girder parameters. The girder weight, stress, local stability, static displacement, and vibration frequency are response values. Constraint conditions are evaluated by examining each factor with response value according to the orthogonal matrix L16. Analysis of the Signal to Noise ratio and ANOVA by Minitab software will select the optimal parameters that satisfy the constraints, the goal is to reduce the volume compared to the original design. The test results of the crane with a lifting capacity of 250 tons, an aperture of 31 m, the girder weight reduced by 24.33 %, while the stress increased by only 6.16 %. The new design ensures suitable local stability conditions by making better use of the material’s capabilities. With the new parameters, the technical criteria are guaranteed.